Agenda for the Compiler Community. (Communications of the ACM, 2009)
The article proposes an agenda for the community of researchers related to computer compilers. A list of proposed research items is presented with the intention of enabling collaborative research between industry, academic institutions, and government funding agencies. Items mentioned include benchmarks for evaluating advances in compliers, methodology for measuring compiler progress, and compilers capable of self-improvement.